FREQUENCY AND RELATED FACTORS CAUSING OBESITY IN SCHOOL GOING CHILDREN OF PESHAWAR: A CROSS SECTIONAL STUDY (Journal of Medical & Health Sciences Review, 2025)
Background: Obesity is a global health concern, particularly among school-going children. This study aimed to assess the prevalence of obesity and overweight in school-going children in Peshawar, Pakistan. Methods: A cross-sectional study was conducted in public and private schools in Peshawar. A total of four schools, including one boys' and one girls' school from rural and urban areas each, were conveniently selected. Participants aged 14 to 17 years from classes’ eighth to tenth were included. Data on height and weight were collected to calculate body mass index (BMI). A standard self-formed questionnaire was used for data collection. The study duration was six months, and data analysis was performed using SPSS version 25. Results: Among the 114 participants, 50% were males and 50% were females. The age range was 14 to 17 years, with a mean of 15.33 years. The baseline characteristics revealed varying distributions of BMI categories across gender, age, and grade groups. No significant association was found between BMI categories and gender or residence. However, a significant association was observed between BMI categories and family income status. Moreover, there was a significant association between BMI categories and the frequency of consuming fast food from takeaway and fizzy drinks. Conclusion: The study revealed significant associations of obesity (df=5%, N=114, &C,I=95%; p0.05).